2016
DOI: 10.1021/acs.est.6b01692
|View full text |Cite
|
Sign up to set email alerts
|

Dual Carbon–Bromine Stable Isotope Analysis Allows Distinguishing Transformation Pathways of Ethylene Dibromide

Abstract: The present study investigated dual carbon-bromine isotope fractionation of the common groundwater contaminant ethylene dibromide (EDB) during chemical and biological transformations, including aerobic and anaerobic biodegradation, alkaline hydrolysis, Fenton-like degradation, debromination by Zn(0) and reduced corrinoids. Significantly different correlation of carbon and bromine isotope fractionation (ΛC/Br) was observed not only for the processes following different transformation pathways, but also for abio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
53
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(68 citation statements)
references
References 61 publications
11
53
4
Order By: Relevance
“…Based on the increase in Br in the aqueous phase and the detection of ethene in the gas phase, and the absence of VB, it was inferred that EDB was converted into Br and ethylene in a two-electron transfer pathway of dihaloelimination (Equation (5)). This observation is consistent with the conclusions from the study of Kuntze et al [13], in which the dual carbon-bromine stable isotope was used to determine the biotransformation pathways of EDB, and it was found that EDB was degraded to ethylene directly in response to Sulfurospirillum multivorans under anaerobic conditions. C2H4Br2+2[H]dihaloeliminationC2H4+2HBr…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Based on the increase in Br in the aqueous phase and the detection of ethene in the gas phase, and the absence of VB, it was inferred that EDB was converted into Br and ethylene in a two-electron transfer pathway of dihaloelimination (Equation (5)). This observation is consistent with the conclusions from the study of Kuntze et al [13], in which the dual carbon-bromine stable isotope was used to determine the biotransformation pathways of EDB, and it was found that EDB was degraded to ethylene directly in response to Sulfurospirillum multivorans under anaerobic conditions. C2H4Br2+2[H]dihaloeliminationC2H4+2HBr…”
Section: Resultssupporting
confidence: 91%
“…The EDB biodegradation efficiency under the relevant groundwater conditions in this study was compared with those observed in previous studies under aerobic or anaerobic conditions by a single species or mixed culture (Table 1). As shown, the majority of previous EDB biodegradation studies were conducted under aerobic conditions by indigenous microorganisms or mixed culture, with a few exceptions under anaerobic conditions [2,12,13]. The present study is the first to explore the potential of enhanced EDB biodegradation under a dynamic DO condition, which was often observed in the engineered field applications.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…where α rp is the fractionating factor at reactive position, ε is bulk enrichment factor, and z is the 103 number of carbon or bromine atoms at reactive positions. In this work we calculated α rp based on 104 the AKIE values reported in Kuntze et al (2016); however, α rp could be also derived by fitting the 105 proposed model to the raw isotope data. 106 We track the concentration change of each isotopologue considering a specific kinetic rate law.…”
mentioning
confidence: 99%